Next Season’s Green Bond Harvest : Innovations in Green Credit Markets - Coston, Elizabeth; Odaro, Esohe Denise; Hartwick, Evelyn; Jones, Jamie (International Finance Corporation, Washington, DC, 2017)
Capital markets have been a source of funding for green investments for a number of years, but until recently, financing was predominantly from equity. Private equity, venture capital, and government funding were the most accessible sources of capital when green technologies such as solar and wind were in early stages of development. More recently, as these technologies have been tested, proven, and refined, funders have naturally progressed along the capital structure towards public equity and debt financing to support growth and scale. At the same time, leading financial institutions have provided impetus for expanded green investing. International Finance Corporation (IFC) and the Kellogg School of Management have collaborated to author this paper which attempts to cover the bounty of credit tools available for harvesting by issuers and sponsors, with the aim of attracting new investments to green industry. This paper is the first in a series to proffer avenues to enhance the financial environment towards addressing this gap. This paper presents a brief overview of efforts that can circumvent these barriers by introducing a mix of innovative products to attract different kinds of fixed income investors and draw more private capital into funding green technologies.